2013
DOI: 10.3892/etm.2013.1337
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and ECG variables in children and adolescents: A cross-sectional study

Abstract: Obesity exhibits a wide variety of electrocardiogram (ECG) abnormalities in adults, which often lead to cardiovascular events. However, there is currently no evidence of an association between obesity and ECG variables in children and adolescents. The present study aimed to explore the associations between obesity and ECG intervals and axes in children and adolescents. A cross-sectional observational study of 5,556 students aged 5–18 years was performed. Anthropometric data, blood pressure and standard 12-lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
2
15
1
9
Order By: Relevance
“…Our study results reveal a positive association between PR interval and both BMI and WHR. This is consistent with reports noting PR interval prolongation with increasing obesity [8,31,32]. In particular, increasing obesity marks increasing pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 81%
“…Our study results reveal a positive association between PR interval and both BMI and WHR. This is consistent with reports noting PR interval prolongation with increasing obesity [8,31,32]. In particular, increasing obesity marks increasing pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 81%
“…This observation confirms with more robust data the results of a previous study which focused on the heart rate and QTc interval of 781 children aged 10–18 years. 17 Overall ECG abnormalities were found more often in males than in females, consistent with other reports, 7–10 with a total prevalence of ECG abnormalities of 22%, close to that found in another Italian study which involved a smaller sample of students. 11 The higher prevalence of an incomplete RBBB reported in underweight subjects and lower rate in obese subjects is consistent with data observed in adults, where the incomplete RBBB was found to be associated with a lower BMI.…”
Section: Discussionsupporting
confidence: 89%
“…Data which are available were largely obtained from adult populations and when adolescents were evaluated, major ECG abnormalities were not systematically assessed. 7 Furthermore, published ECG findings in large young populations were mainly focused on athletes as report of pre-participation evaluation aiming at sudden cardiac death prevention, 8 not systematically dealing with anthropometric parameters 8–11 and in some cases focused on young males in military conscription older than our population. To the best of our knowledge this is the largest report on non-selected adolescents which evaluates ECG and anthropometric characteristics and the first which attempts to assess the correlations between ECG abnormalities and anthropometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…HR rest has been well discussed by many studies on overweight and obese children [18,20,24,61,62,63,64]. HR rest in most of these studies has been measured in a seated position [18,24,26,62,63,65], in a few studies in a supine position [61,64], and position was not reported in one case [20]. HR recording usually lasted from 3 min [24] to 15 min [61].…”
Section: Resultsmentioning
confidence: 99%